Water-level elevation governs iron-bound organic carbon dynamics in a reservoir drawdown zone - Haojun Deng; Zhuangpeng Zheng; Zhi Zhang; Aimin Chen; Guiling Lin (Journal of Soils and Sediments, 2026)

Tailored self-assembled molecule for efficient charge extraction and enhanced crystallization in wide-bandgap perovskite solar cells - Haojun Hu; Xianglang Sun; Xuke Yang; Zongbao Li; Peiyan Zhang; Xinyu Yu; Shi'ang Li; Zifan Lin; Dayu Liu; Ziyang He; Chuyun Deng; Longhui Zeng; et al. (Chemical Engineering Journal, 2026)

Slippage-suppression robot-assisted retraction for thyroid surgery with 5DoF contact force sensing - Shouhui Deng; Haojun Li; Yuxuan Lin; Aiguo Song; Lifeng Zhu (Medical & Biological Engineering & Computing, 2025)

Highly flexible Janus fabric based on TPU spraying and laser processing for personal thermal-wet management - Zixuan Xu; Yulun Wu; Shuqiang Min; Lin Hu; Tonghuan Zhan; Heng Wang; Yan Yuan; Haojun Luo; Yichen Tang; Bing Xu (Chemical Engineering Journal, 2025)

Green synthesis of tea polyphenol grafted epoxypropyl polymer with enhanced mechanical and antifungal benefits for bamboo protection - Haojun Lin; Haiyan Yang; Jing Yang; Dawei Wang; Zhengjun Shi; Chun Shi (Chemical Engineering Journal, 2025)

Salinity as a key factor affects viral structure, function, and life strategies in lakes from arid and semi-arid regions - Haojun Lei; Nuowen Zhou; Jinhong Zhang; Ruifeng Lin; Tianyi Chen; Jiang Wu; Lei Su; Shufeng Liu; Tang Liu (Journal of Hazardous Materials, 2025)

Selective recovery of gold from waste printed circuit boards leachate by modified gel zeolitic imidazolate framework-8 - Haojun Hou; Shuliang Chen; Rongquan Liu; Yue Lin; Xianzhi Hu; Futing Zi (Journal of Environmental Chemical Engineering, 2025)

Mass transfer analysis of a concentration-regulated metal-assisted chemical etching system and its application in Si nanohole fabrication - Jiecai Long; Xuan Zhang; Haojun Zhang; Haoya Wang; Congkai Xie; Xun Chen; Guohuai Lin; Yun Chen; Xin Chen; Huitao Liu; Renquan Lu (Chemical Engineering Journal, 2025)

Effects of cache distribution and size on cache foraging by animals - Ling Hou; Haojun Dou; Mingjie Hu; Lin Cao (Animal Behaviour, 2024)

Construction of anticorrosive coatings with emergency response closure by introducing functionalized graphene oxide - Yuxuan Huang; Shaoheng Yang; Yang Hu; Haojun Lin; Jiesheng Tang; Chang-An Xu; Zhuohong Yang (Chemical Engineering Journal, 2024)

Association of mitochondrial DNA variation with high myopia in a Han Chinese population - Shilai Xing; Siyi Jiang; Siyu Wang; Peng Lin; Haojun Sun; Hui Peng; Jiaying Yang; Hengte Kong; Sheng Wang; Qingshi Bai; Ruowen Qiu; Wei Dai; et al. (Molecular Genetics and Genomics, 2023)
High myopia (HM), which is characterized by oxidative stress, is one of the leading causes of visual impairment and blindness across the world. Family and population genetic studies have uncovered nuclear-genome variants in proteins functioned in the mitochondria. However, whether mitochondrial DNA mutations are involved in HM remains unexplored. Here, we performed the first large-scale whole-mitochondrial genome study in 9613 HM cases and 9606 control subjects of Han Chinese ancestry for identifying HM-associated mitochondrial variants. The single-variant association analysis identified nine novel genetic variants associated with HM reaching the entire mitochondrial wide significance level, including rs370378529 in ND2 with an odds ratio (OR) of 5.25. Interestingly, eight out of nine variants were predominantly located in related sub-haplogroups, i.e. m.5261G > A in B4b1c, m.12280A > G in G2a4, m.7912G > A in D4a3b, m.94G > A in D4e1, m.14857 T > C in D4e3, m.14280A > G in D5a2, m.16272A > G in G2a4, m.8718A > G in M71 and F1a3, indicating that the sub-haplogroup background can increase the susceptible risk for high myopia. The polygenic risk score analysis of the target and validation cohorts indicated a high accuracy for predicting HM with mtDNA variants (AUC = 0.641). Cumulatively, our findings highlight the critical roles of mitochondrial variants in untangling the genetic etiology of HM.

Identification of Large Yellow Croaker under Variable Conditions Based on the Cycle Generative Adversarial Network and Transfer Learning - Shijing Liu; Cheng Qian; Xueying Tu; Haojun Zheng; Lin Zhu; Huang Liu; Jun Chen (Journal of Marine Science and Engineering, 2023)
Variable-condition fish recognition is a type of cross-scene and cross-camera fish re-identification (re-ID) technology. Due to the difference in the domain distribution of fish images collected under different culture conditions, the available training data cannot be effectively used for the new identification method. To solve these problems, we proposed a new method for identifying large yellow croaker based on the CycleGAN (cycle generative adversarial network) and transfer learning. This method constructs source sample sets and target sample sets by acquiring large yellow croaker images in controllable scenes and actual farming conditions, respectively. The CycleGAN was used as the basic framework for image transformation from the source domain to the target domain to realize data amplification in the target domain. In particular, IDF (identity foreground loss) was used to optimize identity loss judgment criteria, and MMD (maximum mean discrepancy) was used to narrow the distribution between the source domain and target domain. Finally, transfer learning was carried out with the expanded samples to realize the identification of large yellow croaker under varying conditions. The experimental results showed that the proposed method achieved good identification results in both the controlled scene and the actual culture scene, with an average recognition accuracy of 96.9% and 94%, respectively. These provide effective technical support for the next steps in fish behavior tracking and phenotype measurement.

Wind and salt spray alter tree shape and dry mass density in Casuarina equisetifolia L. - Yongming Lin; Jian Li; Jonathan D. Bakker; Han Lin; Can Chen; Wei Hong; Loretta Fisher; Chengzhen Wu; Tao Hong; Haojun Deng; Guangshuai Zhang; Kun Du (Trees, 2017)